The benefits and costs of import substitution in India : a microeconomic study - Krueger, Anne O. (Minneapolis : University of Minnesota Press, 1975)
This study examines the benefits and costs of import substitution in India. The research design was formulated to check the estimation both in practicability and reliability.
On spine: Import substitution in India.
Includes bibliographical references and index.
asm 24/01/2019
Loans
Keywords: Automobile supplies industry; Automobile industry and trade; Foreign trade regulation; Industries; Import substitution; India